Unveiling the Layer‐Dependent Catalytic Activity of PtSe2 Atomic Crystals for the Hydrogen Evolution Reaction. Issue 21 (12th April 2019) - Hu, Dake; Zhao, Tianqi; Ping, Xiaofan; Zheng, Husong; Xing, Lei; Liu, Xiaozhi; Zheng, Jingying; Sun, Lifei; Gu, Lin; Tao, Chenggang; Wang, Dong; Jiao, Liying
Abstract: Two‐dimensional (2D) PtSe2 shows the most prominent layer‐dependent electrical properties among various 2D materials and high catalytic activity for hydrogen evolution reaction (HER), and therefore, it is an ideal material for exploring the structure–activity correlations in 2D systems. Here, starting with the synthesis of single‐crystalline 2D PtSe2 with a controlled number of layers and probing the HER catalytic activity of individual flakes in micro electrochemical cells, we investigated the layer‐dependent HER catalytic activity of 2D PtSe2 from both theoretical and experimental perspectives. We clearly demonstrated how the number of layers affects the number of active sites, the electronic structures, and electrical properties of 2D PtSe2 flakes and thus alters their catalytic performance for HER. Our results also highlight the importance of efficient electron transfer in achieving optimum activity for ultrathin electrocatalysts. Our studies greatly enrich our understanding of the structure–activity correlations for 2D catalysts and provide new insight for the design and synthesis of ultrathin catalysts with high activity. Abstract : Through thick and thin : Since the thickness of two‐dimensional (2D) PtSe2 flakes can be controlled by adjusting synthesis conditions, their layer‐dependent catalytic activity for the hydrogen evolution reaction could be investigated from both theoretical and experimental perspectives. Structure–activity correlations were drawn, providing new insights for the design and synthesis of ultrathin catalysts.